Catchment and climatic influences on spatio-temporal variations in suspended sediment transport dynamics in rivers - Shin, Jae hun; Grabowski, Robert C.; Holman, Ian P. (IWA Publishing, 2023)
Suspended sediment concentration (SSC) is an important attribute for water resources management. However, the interactions between climate and catchment characteristics that control the temporal variability of SSC in rivers are not fully resolved. The study aim is to evaluate how these variables influence spatial and seasonal variations in SSC dynamics at a continental scale. Daily SSC (mg/l) and site attribute data from 120 sites (USA) with minimum 10 years of record (1971–2000) were analysed. New indicators of SSC dynamics (magnitude and frequency) were developed and applied annually and seasonally. Geographically weighted regression (GWR) models were created for each ordinary least squares (OLS) regression model, and GWR coefficients were analysed by ecoregion. Land cover, rainfall and erosivity, baseflow index and soil texture were the most common variables in the OLS models. GWR coefficients displayed significant variation across the continent. Agricultural cover was positively associated with low frequency SSC events, while urban and forest cover predicted higher frequency events, except in the desert areas. PPT30 was generally a negative predictor for SSC magnitude, except the marine west coasts forests. These findings on catchment and climate controls on SSC will support future predictive models of SS transport dynamics.
Keywords: catchment; climate; land cover; land use; sediment yield; suspended sediment concentrations